Racially biased policing and neighborhood characteristics: A Case Study in Toronto, Canada - Meng, Yunliang (Cybergeo, 2014)
This study investigated race-and-place profiling in Toronto within a neighborhood context. It explored the spatial association between race-specific drug-related stops and neighborhood racial and socio-economic characteristics. The findings of this study suggest that Blacks are subject to disproportionately more stops for drug-related reasons in neighborhoods where more Whites reside and are less socio-economically disadvantaged, therefore confirming race-and-place profiling of Blacks in Toronto. However, race concentration and socio-economic disadvantage arguments fail to explain the spatial variations in drug-related stops of Whites. This result could be caused by the diverse ethnic origins and socio-economic backgrounds of White Torontonians. This article argues for the importance of a contextualized examination of racial profiling within the spatial context of neighborhoods and calls for democratic policing in Toronto. It also discusses the negative impacts of race-and-place profiling on Blacks in Toronto.